The Church in the power of the spirit - Keswick 2006; Hull, Ali (London: Authentic Media, 2006)
What is God's plan for the Church? How does the Holy Spirit work to bring it about? This title presents a collection of teachings from the 2006 Convention.
Keywords: Keswick movement -- Congresses